The Relationship between Parity and Family Support in Pregnant Women's Participation in Pregnancy Exercises at the Eka Sriwahyuni Maternity Clinic, Medan Denai District, Medan City - Siregar, Eka Sylviana; Mawaddah, Maulina (International Journal of Medicine And publich Health, 2024)
Pregnancy exercise classes are a means of learning about health for pregnant women, in face-to-face form. This program aims to increase mothers' knowledge and skills regarding pregnancy exercise. To identify the relationship between parity and family support with the participation of pregnant women in taking part in Pregnancy Gymnastics at the Eka Sriwahyuni ​​Clinic, Medan Denai District, Medan City. This type of research is analytical with a cross sectional design. The sample in this study was all existing pregnant women, namely 30 people, with a sampling technique using total sampling. The data collection tool in this research uses a questionnaire. The data analysis used is univariate and bivariate analysis. The research results showed that there was a parity relationship with the participation of pregnant women in taking part in pregnancy exercise with a P value of 0.028 and there was family support with the participation of pregnant women in taking part in pregnancy exercise with a P value of 0.028. It is hoped that health workers, especially midwives, will be more active in disseminating information about pregnancy exercise programs not only to pregnant women, but also to husbands/partners and families by increasing all components of family support.